Case report: Dihydropyridine receptor (CACNA1S) congenital myopathy, a novel phenotype with early onset periodic paralysis - Aburahma, Samah K.; Rousan, Liqa A.; Shboul, Mohammad; Biella, Fabio; Lucchiari, Sabrina; Comi, Giacomo Pietro; Meola, Giovanni; Pagliarani, Serena (Frontiers in Neurology, 2024)
Introduction CACNA1S related congenital myopathy is an emerging recently described entity. In this report we describe 2 sisters with mutations in the CACNA1S gene and the novel phenotype of congenital myopathy and infantile onset episodic weakness. Clinical description Both sisters had neonatal onset hypotonia, muscle weakness, and delayed walking. Episodic weakness started in infancy and continued thereafter, provoked mostly by cold exposure. Muscle imaging revealed fat replacement of gluteus maximus muscles. Next generation sequencing found the missense p.Cys944Tyr variant and the novel splicing variant c.3526-2A>G in CACNA1S. Minigene assay revealed the splicing variant caused skipping of exon 28 from the transcript, potentially affecting protein folding and/or voltage dependent activation. Conclusion This novel phenotype supports the notion that there are age related differences in the clinical expression of CACNA1S gene mutations. This expands our understanding of mutations located in regions of the CACNA1S outside the highly conserved S4 segment, where most mutations thus far have been identified.